Fatores condicionantes da flora marginal e aquática do estuário do rio Massaguaçu (Caraguatatuba – SP) - Ribeiro, José Pedro Nepomuceno (2007)
Both the biotic and abiotic characteristics of a habitat determine which species can live in this habitat. The frontier of two different habitats creates a transition zone, called ecotone. The transition of the Atlantica Forest and the Restinga is normally related to the presence of salt. The salt is a border line for vegetation. In costal habitats, the salt spray increases the salt in the soil, besides having a direct effect on the vegetations tissues. Riparian vegetation on the other hand, has its characteristics linked with the characteristics of the adjacent water bodies. We worked in an estuary in Caraguatatuba, São Paulo, where the Atlantic and Restinga Forests co-occurs in its margins. Our objective was to determine how the salt spray and the estuary water influence the composition of the vegetation of the arboreal component of its margins. Our results show abiotic and floristical composition differences between three different ambients. The characteristics of the estuary water and soil have little influence and the salt spray has great influence on the separation of these ambients, but the salt spray did.